2020
DOI: 10.18632/aging.104117
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anti-osteoporosis treatments on the incidence of COVID-19 in patients with non-inflammatory rheumatic conditions

Abstract: Coronavirus disease 19 (COVID-19) is currently a global pandemic that affects patients with other pathologies. Here, we investigated the influence of treatments for osteoporosis and other non-inflammatory rheumatic conditions, such as osteoarthritis and fibromyalgia, on COVID-19 incidence. To this end, we conducted a cross-sectional study of 2,102 patients being treated at the Rheumatology Service of Hospital del Mar (Barcelona, Spain). In our cohort, COVID-19 cumulative incidence from March 1 to May 3, 2020 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 34 publications
4
39
0
6
Order By: Relevance
“…Studies that were adjusted ( n = 3) ( 39–41 ) (OR: 1.77; 95% CI: 1.24, 2.53; I 2 : 44.2%; Figure 2 A ) and nonadjusted for confounders ( n = 5) ( 42–45 , 46 ) (OR: 1.75; 95% CI: 1.44, 2.13; I 2 : 33%; Figure 2B ) indicated higher risk of infection in the VDD group ( Figure 2 ). The Blanch-Rubió et al ( 37 ) study was not included in analysis, because of a different design. This study was a cross-sectional study including 2102 patients with noninflammatory rheumatic conditions and found that no association between intake of vitamin D supplement and COVID-19 (risk ratio: 0.91; 95% CI: 0.62, 1.34).…”
Section: Resultsmentioning
confidence: 99%
“…Studies that were adjusted ( n = 3) ( 39–41 ) (OR: 1.77; 95% CI: 1.24, 2.53; I 2 : 44.2%; Figure 2 A ) and nonadjusted for confounders ( n = 5) ( 42–45 , 46 ) (OR: 1.75; 95% CI: 1.44, 2.13; I 2 : 33%; Figure 2B ) indicated higher risk of infection in the VDD group ( Figure 2 ). The Blanch-Rubió et al ( 37 ) study was not included in analysis, because of a different design. This study was a cross-sectional study including 2102 patients with noninflammatory rheumatic conditions and found that no association between intake of vitamin D supplement and COVID-19 (risk ratio: 0.91; 95% CI: 0.62, 1.34).…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis of fourteen studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36] showed that patients with RD had a significantly higher risk of developing COVID-19 than the general population (OR = 1.53, 95% CI 1.24-1.88, P = 0.000; I 2 = 62.4%, P = 0.001) ( Fig. 2).…”
Section: Risk Of Covid-19 Infection In Rheumatic Diseasesmentioning
confidence: 99%
“…Multi-omic analyses of published datasets have identified vitamin D (among a suite of other candidates) as a potential prophylactic agent for COVID-19 (244). However, being treated with vitamin D, did not significantly change the incidence of COVID-19 in a study of >2,000 people treated for non-inflammatory rheumatic conditions (Mar-May 2020) (245).…”
Section: Vitamin D Status and Covid-19mentioning
confidence: 99%